Pedagogical Practice as a Precondition of Perfection of Future Teacher’s Communication Competence - Aukštkalnytė, Dėja (Acta Paedagogica Vilnensia, 2001)
To spread all innovations in Lithuanian educational system is the task of active and progressive teachers. One of the main goals of nowadays-pedagogical school is to prepare students to be better communicators. The problem is that in programs of Lithuanian Universities predominate theoretical disciplines. Students of music teachers' speciality during their studies are lacking the close involvement into everyday school life. Pedagogical practice is one of disciplines which helps them to develop their communication with pupils and at the same time to rise perceptions, communicational and interactional skills. This is the basic of the communication competence of students' and future music teachers'. The main goal of this article is to reveal the actuality of pedagogical practice and to show its' role in development of communicational skills of future teachers. The researches indicate that there is a close connection between pedagogical practice and development of communicational skills. Particularly perceptional and communicational skills are better of these students who had pedagogical practice in secondary school. Students and teachers suffer main difficulties working with teenagers (V-IX grades). Reasons of these difficulties are different but teachers have more foresights about the problem. More than third part of all respondents are not satisfied about their pedagogical communication today. They have many suggestions how to raise the role of pedagogical practice. Almost half of music teachers answered that at the time of their studies they had not enough practice to be prepared to their work at school. So the main conclusion is that pedagogical practice is one of the most important factors which can improve the communication competence of future music teachers.
Keywords: Higher education; teacher education; pedagogical practice; communication competence; communicational skills.